Aflibercept for diabetic macular edema. (August 2014) - Udaondo, Patricia; Garcia-Delpech, Salvador; Matinez-Costa, Rafael; Navarro-Piera, Juan; Cisneros-Lanuza, Angel
Abstract : Different intravitreal anti-VEGF medications have been used for the management of retinal vascular disorders with highly satisfactory results and good safety profiles. Aflibercept, a new anti-VEGF drug with a different mechanism of action compared with prior therapies, has recently emerged. The results of aflibercept Phase II and III studies show its efficacy for the treatment of wet age-related macular degeneration, macular edema secondary to central retinal vein occlusion and diabetic macular edema.